Azimuth-track level compensation to reduce blind-pointing errors of the Deep Space Network antennas. - Gawronski, Wodek; Baher, Farrokh; Quintero, Ofelia
The 34-meter antennas of the NASA Deep Space Network are ?wheel and track? antennas. The latter term refers to a set of wheels at the base of the structure, which roll on a circular steel track supported by a concrete foundation ring. The track is assumed flat; however, its level varies due to manufacturing imperfections, structural loads, non-uniformity of the soil, and temperature variations. It is specified that the deviations of the azimuth-track level shall not exceed ±0.5 mm. During tracking, this amplitude of deviations causes deformations of the antenna structure, resulting in pointing errors of ±2 mdeg, which exceed the required accuracy for 32-GHz (Ka-band) tracking. However, structural deformations caused by the azimuth track unevenness are repeatable; therefore, a look-up table can be created to improve the blind-pointing accuracy. This paper presents the process for creation of the look-up table, describes the instrumentation necessary for determining the pointing errors, and describes the processing of inclinometer data. It derives algorithms for the pointing-error estimation, and for the azimuth-axis tilt using the inclinometer data. It compares the error corrections based on the created look-up table and actual measurements of pointing errors using the conical scanning (conscan) technique. This comparison shows a satisfactory convergence that justifies the implementation of the approach in forthcoming NASA missions.
Keywords: Space vehicle tracking; Scanning antennas; Pointing systems; Antenna mechanical factors; Antenna tolerance analysis; Satellite communication; Satellite tracking